Do donors respond to discretionary accounting information consolidation?. Issue 1 (5th March 2018) - Quosigk, Benedikt; Forgione, Dana A.
Abstract : Purpose: The purpose of this paper is to investigate donor responses to discretionary accounting information consolidation. Nonprofit (NP) financial statement consolidation discretion significantly impacts program ratio reporting, the primary NP performance measure. Stakeholders are misled to allocate limited resources inefficiently. While some NPs file group Internal Revenue Service (IRS) Form 990 returns with their affiliates, effectively providing consolidated statements, others choose to file independently of their affiliates. Design/methodology/approach: The authors use OLS regression analysis and panel data for 5, 697 NP-year observations for the period 2009-2011 retrieved from the National Center for Charitable Statistics Form 990 database. Findings: The authors find evidence that consolidation discretion substantially impacts donor decisions. NP managers have incentive to utilize consolidation discretion to influence charitable giving. Practical implications: The authors urge the IRS and the Financial Accounting Standards Board to reconsider the consolidation guidance for NP organizations, to develop performance measures beyond the widely used program ratio, and to require program ratio segment reporting to allow for better comparability among NPs irrespective of consolidation status. Further, the authors caution stakeholders to consider supporting organization transactions in their resource allocation decisions. Originality/value: The authors are the first to use NP supporting organization information to investigate consolidation discretion and its impact on donor responses.